The Impact of Online Video Cases on Clinical Reasoning in Occupational Therapy Education: A Quantitative Analysis - Lynne F. Murphy; Wendy B. Stav (Scholarworks @ WMU, 2018)
Clinical reasoning, the cognitive process of a skilled occupational therapist, is a complex and necessary component of evaluating clients and implementing interventions that facilitate each client's achievement of relevant and meaningful participation in daily occupations. Clinical reasoning encompasses a set of skills that must be integrated into college curricula for the preparation of occupational therapists, but it is not easily taught in a classroom setting. This quasi-experimental, quantitative research explored how specific instructional techniques, constructed on the tenets of case-based reasoning, influenced the development of clinical reasoning in occupational therapy students. The experimental group with video cases improved significantly in overall reasoning. The video cases challenged the learners to analyze their observations, explicitly identify clinical reasoning skills, and make decisions regarding occupational therapy interventions and services. This may influence how video technology is used and integrated into didactic educational practices.